Determinants of Commercial Banks’ Lending Behavior in Nepal - Bhattarai, Bishnu Prasad (International Journal of Accounting & Finance Review, 2019)
The main objective of this study was to establish the determinants of lending operations among commercial banks in Nepal. Specifically, the study sought to explore the effect of bank specific characteristics and to identify external factors that determine commercial banks’ lending behavior in Nepal. Secondary panel data was used that covered a period of six years (2012/13-2017/18) of the major ten commercial banks to examine factors associated with lending behavior of in Nepal. From the estimation results, it was found that liquidity ratio, interest rate spread and exchange rate were significant in determining lending behavior in Nepal’s commercial banks. The positive effect of exchange rate infers that commercial banks in Nepal have sufficient insights into the international market and trade and that they are prepared to meet short-term and long-term commitments. Inflation maintained by the central economic policy has a positive and significant influence on lending volumes among commercial banks in Nepal. Likewise, the findings showed interest rate spread negatively and significantly on total loans advanced to individual and institutions. This implies that as the cost of borrowing increases, banks significantly increase credit supply in the market. However, there seems a greater deal of reluctance from among the borrowers to get more credit in such situations. During periods of economic stagnation, majority of loans become non-performing and thus constraining credit available to private sector.